Global and Multicultural Education: A Necessity in the Globalization Era - Rismayani, Rismayani; Kania, Nia (EDUPEDIA Publisher, 2024)
Global and multicultural education is a crucial element in addressing the issues of the globalization period. This article examines the principles, obstacles, and remedies of implementing global and multicultural education. A qualitative method and literature evaluation reveal that global education equips students to engage in critical thinking and ethical action within an international framework. Simultaneously, multicultural education underscores the significance of inclusivity and reverence for cultural diversity. Case studies from Finland, Singapore, and Canada demonstrate their efficacy in incorporating this education into the national curriculum. Nonetheless, cultural hostility, insufficient teacher preparation, and economic disparity among nations persist as substantial impediments. Proposed solutions encompass the creation of flexible curricula, rigorous teacher training, international cooperation, and community education initiatives. This essay contends that global and multicultural education cultivates internationally competitive individuals while fostering the establishment of a just and inclusive society.